Making disappearance visible? Photographs of the disappeared at the ESMA on Victor Basterra’s testimony (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Víctor Basterra, an ESMA survivor, was able to take away from this detention clandestine center a substantial number of photographs, rolls of film, and other documents, which were meant to be destroyed by the military. The images of the ESMA, taken from the inside, have come together with Basterra’s words on his long testimonial career, since its be- ginning in 1984, every time he has presented his testimony somewhere. Over the years, however, the relationship bet- ween word and image has changed; the photographs have taken new meanings, and the figure of Basterra as a witness has been connected to those photographs in a variety of ways. How are word and image intertwined in different pe- riods?What meanings do those photos take over time?What value are the photographs given by the witness on each of his statements?This article analyzes the first time those pictures were shown to the public on two documents in 1984 and 1985. In addition, it compares them to a book made 20 years later in 2005, and to a 2007 photo exhibition.
Keywords: Testimony; Photography; ESMA; Dictatorship; Argentina